SOCIAL INTERACTION BETWEEN STUDENTS OF DRUG PECANDUES IN GROWING SELF-CONFIDENCE: Case Study of Drug Rehabilitation Students at Ar-Rahman Islamic Boarding School - Malik, Adam; Annur, Saipul; Handayani, Tutut (Conciencia, 2023)
This study aims to describe the process of social interaction between ex-drug addict students and non-drug addict students at school, to analyze the behavior of ex-drug addict and non-drug addict students influencing each other in the process of social interaction at school, to analyze the behavior of ex-drug addict students in fostering a sense of self-confidence in the process of interacting between the two at school naturally the purpose of this research will be collected through observation, interviews and documentation. This research includes a type of skinative approach. Data obtained using interviews, observation and documentation. Data analysis techniques used in this research are data collection, data reduction, data presentation, conclusion drawing and leveraging. The results of this study indicate that interactions between former drug addict and non-drug addict students occur in the learning process, where non-drug addict students are more active in speaking than former drug addict students. The activeness of listening and responding to interlocutors of both individual students is the same. The interaction skills of ex-drug addict and non-drug addict students show different abilities between the two groups, but show almost the same ability seen from individuals with individuals in the group. Ex-drug addict students are the same as other drug addict students when working with non-addict students, namely sometimes inferior and more silent, in contrast to non-addict students who are more courageous and focused when working together. They interact with their group more easily than interacting with friends who are different from their group characters. The dominant behavior patterns that influence ex-drug addict and non-addict students in interacting are different. The behavior of former students is dominant in the aspects of avaluation, control, and neutral. Meanwhile, drug addict students are dominated by control and certainty behavior. Ex-addict students are influenced by feelings of inferiority, while non-addict students are dominated by feelings of high self-confidence.